Fates of imine intermediates in radical cyclizations of N-sulfonylindoles and ene-sulfonamides - Zhang, Hanmo; Hay, E. Ben; Geib, Stephen J.; Curran, Dennis P. (Beilstein Journal of Organic Chemistry, 2015)
Two new fates of imine intermediates formed on radical cyclizations of ene-sulfonamides have been identified, reduction and hydration/fragmentation. Tin hydride-mediated cyclizations of 2-halo-N-(3-methyl-N-sulfonylindole)anilines provide spiro[indoline-3,3'-indolones] or spiro-3,3'-biindolines (derived from imine reduction), depending on the indole C2 substituent. Cyclizations of 2-haloanilide derivatives of 3-carboxy-N-sulfonyl-2,3-dihydropyrroles also presumably form spiro-imines as primary products. However, the lactam carbonyl group facilitates the ring-opening of these cyclic imines by a new pathway of hydration and retro-Claisen-type reaction, providing rearranged 2-(2'-formamidoethyl)oxindoles.
Keywords: ene-sulfonamide; imine; radical cyclization; radical fragmentation; spiro-indoles